A CONVERSATIONAL ANALYSIS OF TURN-TAKING STRATEGIES USED IN BROWNIS TALK SHOW - Nopriani, Rahmi; Afrilesa, Rini; Oktariza, Dodi (Universitas Muara Bungo, 2023)
This research analyzes turn-taking strategies used in Brownis talk show. The objectives of this research are (1) to identify the kinds of turn-taking strategies used by the hosts and the guest in Brownis talk show and (2) to analyze the functions of turn-taking strategies used by the hosts and the guest in Brownis talk show. The analysis is based on the theory by Sacks and Schegloff (1979) on Turn-Taking. The research applied descriptive qualitative method, which uses words to explain the data obtained from the talk show. Tables and figures are also used to present the results and to make it easier for readers to understand.